2021
DOI: 10.1097/hjh.0000000000002730
|View full text |Cite
|
Sign up to set email alerts
|

Central pulse pressure is inversely associated with proximal aortic remodelling

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
3
9
0
Order By: Relevance
“…[19] A 20-year follow-up study discovered that aortic diameter was positively associated with LV mass. [8] Our study also demonstrated a strong and stable positive association between AoR and LVMI. Yet, it seems contradictory that aortic dilatation can reduce arterial load, which is positively correlated with LVH.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…[19] A 20-year follow-up study discovered that aortic diameter was positively associated with LV mass. [8] Our study also demonstrated a strong and stable positive association between AoR and LVMI. Yet, it seems contradictory that aortic dilatation can reduce arterial load, which is positively correlated with LVH.…”
Section: Discussionsupporting
confidence: 71%
“…A study demonstrated that the group with the normal aorta and higher PWV had the highest risk of cardiovascular disease in the community population, especially males. [10] Aortic dilatation is related to LV remodeling, impaired diastolic function, and cardiovascular events; [8,18] however, the exact role ascending aortic dilatation has in regulating LV afterload remains debatable. PP is used clinically as the surrogate of arterial pulsatile pressure load.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We based on the hypothesis that the descending aorta does not appear to have an acute dilatation before aortic dissection, but as a matter of fact, it is difficult to validate the hypothesis as we can barely obtain the data just before aortic dissection happens. In terms of research design, the sample size is still not enough, and the features we take into account are not comprehensive, such as NT-ProBNP, C-reaction protein, hereditary background, central pulse pressure ( 22 , 27 29 ), etc. In addition, the model we established requires too many parameters to be used conveniently in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we presented a numerical investigation of the effects of the computational model’s inlet and outlet boundary conditions on computed CT-FFR. The mean pressure calculated by the “physiological formula” differed from the real aortic pressure wave ( Tosello et al, 2021 ). However, the calculation model was not sensitive to the boundary conditions of the inlet pressure, i.e., the true aortic pressure could be replaced by the mean pressure calculated by the “physiological formula.” The findings revealed that distal boundary conditions (hyperemic vasodilation response of coronary micro-vessels) have a significant impact on FFR.…”
Section: Discussionmentioning
confidence: 99%